The differential effects of low birth weight and Western diet consumption upon early life hepatic fibrosis development in guinea pig. (17th February 2016) - Sarr, Ousseynou; Blake, Alexandra; Thompson, Jennifer A.; Zhao, Lin; Rabicki, Katherine; Walsh, Joanna C.; Welch, Ian; Regnault, Timothy R. H.
Abstract : Key points: Postnatal intake of a high saturated fat/high sugar diet, the Western diet (WD), is a risk factor for liver fibrosis. Recently, adverse in utero conditions resulting in low birth weight (LBW) have also been associated with postnatal fibrosis development. We demonstrate that suboptimal in utero conditions resulting in LBW are associated with changes in hepatic profibrotic genes in conjunction with minimal liver fibrosis in young non‐overweight adult guinea pigs. Our results also indicate that WD promotes liver steatosis, enhanced expression of hepatic genes and proteins of the proinflammatory, profibrotic, cell death and collagen deposition pathways in conjunction with mild hepatic fibrosis. Our data highlight that pathways responsible for the initiation of a profibrotic state and ultimately hepatic fibrosis appear different depending upon the insult, an in utero ‐induced LBW outcome or a postnatal WD exposure. Abstract: Postnatal intake of an energy dense diet, the Western diet (WD), is a strong risk factor for liver fibrosis. Recently, adverse in utero conditions resulting in low birth weight (LBW) have also been associated with postnatal fibrosis development. We assessed the independent and possible synergistic effects of placental insufficiency‐induced LBW and postnatal WD consumption on liver fibrosis in early adulthood, with a specific focus on changes in inflammation and apoptosis pathways in association with fibrogenesis. Male LBW (uterine artery ablation) and normal birth weight (NBW) guinea pig pups were fed either a control diet (CD) or WD from weaning to 150 days. Significant steatosis, mild lobular inflammation, apoptosis and mild stage 1 fibrosis (perisinusoidal or portal) were evident in WD‐fed offspring (NBW/WD and LBW/WD). In LBW/CD versus NBW/CD offspring, increased transforming growth factor‐beta 1 and matrix metallopeptidase mRNA and sma‐ and Mad‐related protein 4 (SMAD4) were present in conjunction with minimal stage 1 portal fibrosis. Further, connective tissue growth factor mRNA was increased and miR‐146a expression decreased in LBW offspring, irrespective of diet. Independent of birth weight, WD‐fed offspring exhibited increased expression of fibrotic genes as well as elevated inflammatory and apoptotic markers. Moreover, the augmented expression of collagen, type III, alpha 1 and tumor necrosis factor‐alpha was associated with increased recruitment of RNA polymerase II and enhanced histone acetylation (K9) to their respective promoters. These data support a role for both LBW and postnatal WD as factors contributing to hepatic fibrosis development in offspring through distinct pathways. Key points: Postnatal intake of a high saturated fat/high sugar diet, the Western diet (WD), is a risk factor for liver fibrosis. Recently, adverse in utero conditions resulting in low birth weight (LBW) have also been associated with postnatal fibrosis development. We demonstrate that suboptimal in utero conditions resulting in LBW are associated with changes in hepatic profibrotic genes in conjunction with minimal liver fibrosis in young non‐overweight adult guinea pigs. Our results also indicate that WD promotes liver steatosis, enhanced expression of hepatic genes and proteins of the proinflammatory, profibrotic, cell death and collagen deposition pathways in conjunction with mild hepatic fibrosis. Our data highlight that pathways responsible for the initiation of a profibrotic state and ultimately hepatic fibrosis appear different depending upon the insult, an in utero ‐induced LBW outcome or a postnatal WD exposure.